The problem of family disintegration: the imperative for heeding the soft side of Islamic law - Haneef, Sayed Sikandar Shah (2016)
Marriage breakdowns and family instability with their debilitating after-effects on women and children are the hallmark of greatly mechanized global community at present time. To remedy the situation, social scientists have diagnosed a multitude of variables as the precursor of the upward trends in marriage breakdowns and family disintegration. In Malaysian context, women`s financial independence, easy access to multimedia and early marriage are among the factors which count for the rising phenomenon of divorce even during the early years of marriage among Muslims. To remedy the situation, marriage counselling, law reform and pre-marriage courses are mostly emphasized by both mainstream legal scholars and women right activists. It is my considered opinion that these formalistic approaches if not integrated with the soft side of Islamic law may cause more marriage breakups than enhancing families. The bigger issues in terms of soft side of Islamic law, such as marriage fidelity, sense of commitment to care for women and children, and spousal mutual empathy and responsibility, may help a great deal in acculturating our social fabric from early childhood to adolescence and through adulthood. The paper, therefore, argues for the strategic use of the soft side of Islamic law in order to give effect and meaning to formalistic social and legal measures to stabilize families and achieve social cohesion.